PROGRAM IPTEK BAGI PENGURUS BADAN PENGELOLA SARANA PENYEDIAAN AIR MINUM DAN SANITASI (BP SPAMS) TIRTO WENING DI DESA KEDUNGSUMUR - Muchammad Tamyiz; Waluyo Prasetyo; Fuad Achmadi (Journal of Science and Social Development, 2018)
Kedungsumur village is one of the villages in the Krembung Sub-district of Sidoarjo Regency which has problems with the provision of clean water. Since 2014 the Kedungsumur village has received assistance from the local government in the form of deep wells to meet the needs of clean water. The clean water supply system is then managed by an agency called the Management Agency for Water Supply and Sanitation Facilities (MAWSSF) Tirto Wening. As time went by, the number of MAWSSF Tirto Wening clean water customers continued to increase which caused difficulties for administrators to recap their income and monthly expenses. In addition, the BP SPAMS management did not know the direction of the target to be achieved the following year. By this meeting, through the community partnership program from Kemenristekdikti, will provide science and technology assistance to improve the MAWSSF and at the same time provide an overview through simulation of future income and expenditure by using data pre-existing data. The results of this community partnership program show that customer identification in the form of tables has specified the address, the last date of payment, and the total volume of clean water usage, the number of customers until June 2018 there are 234 new customers, and the simulation results show that in January 2018 the board Manager of Water Supply and Sanitation Facilities (MAWSSF) Tirto Wening has been able to affix a profit of Rp.4,560,000.00.